1976
DOI: 10.3109/14017437609167797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Open-Heart Surgery on Intellectual Function

Abstract: Scund J Thor Crirdror,rr\~ Sulk' lo Scand Cardiovasc J Downloaded from informahealthcare.com by University of Otago on 01/03/15 For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…Aberg and Kihlgren in 1974 studied the neuropsychological outcome in 113 patients undergoing surgery with ECC and a control group of 46 patients operated upon for general thoracic surgical conditions. 17 Patients both with and without clinically evident cerebral complications in the ECC group showed significant deterioration in mean neuropsychological scores at 1 week after operation. The control group showed improvement in the mean scores for 4 subtests and a nonsignificant decrease for 2.…”
Section: Discussionmentioning
confidence: 89%
“…Aberg and Kihlgren in 1974 studied the neuropsychological outcome in 113 patients undergoing surgery with ECC and a control group of 46 patients operated upon for general thoracic surgical conditions. 17 Patients both with and without clinically evident cerebral complications in the ECC group showed significant deterioration in mean neuropsychological scores at 1 week after operation. The control group showed improvement in the mean scores for 4 subtests and a nonsignificant decrease for 2.…”
Section: Discussionmentioning
confidence: 89%
“…During the course of a week, clinical evidence of brain dysfunction resolved completely, or nearly so. Those who have recorded cerebral damage in patients after CPB have likewise reported that the condition in most cases is self-correcting (Tufo et al, 1970;Aberg, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Although cerebral damage after heart surgery can be permanent, the evidence is that it is often transient (Tufo et al, 1970;Aberg, 1974;Branthwaite, 1975). We wondered if the clinical evidence of transient cerebral dysfunction might be associated with a transient morphological 736 alteration in the brain microvasculature.…”
mentioning
confidence: 99%
“…On the basis of their performance on a battery of six tests administered preoperatively, 8 days after surgery, and again 8 weeks after surgery, Aberg and Khilgren concluded that arterial line filters confer a degree of protection against cerebral injury during CPB. 8 On theoretical grounds arterial line filters might prevent cerebral damage by removing microemboli from the circulation. In dogs a rise in cerebrospinal fluid brain creatine phosphokinase can be demonstrated during CPB.…”
mentioning
confidence: 99%